From Humor to Strategy: An Experimental Survey on Internet Memes in Social Media Marketing - Mateusz Kiljańczyk; Agnieszka Kacprzak (European Management Studies)
Purpose: The paper addresses the issue of the use of Internet memes as a marketing communication tool in social media. The effectiveness of this type of communication is an important issue due to the large role of memes in digital culture, and at the same time the small number of studies on the use of memes in marketing communication. Design/methodology/approach: To verify the research hypotheses, a survey with an experimental design was conducted among 153 respondents. For the purposes of the study, effectiveness was understood as the ability of a message to induce the passage of the recipient through all stages of perception of the persuasive message, with the last stage being the acceptance of the sender’s outlook. Findings: The results of the study allowed us to draw conclusions about greater effectiveness of marketing communication using Internet memes in comparison to marketing communication without memes. The level of consumer interest in Internet memes turned out to be a differentiating factor in the perception of the form of marketing communication. Research limitations/implications: The main limitation of the study is the non-representativeness of the research sample. The practical implications of the study include guidance on the use of memes when conducting marketing communication on the Internet, taking into account preferences of the target group. Originality/value: This paper not only contributes importantly to the limited literature on Internet memes in marketing activities, but also turns the spotlight onto the characteristics of consumers who are the potential target group of such communication.